(untitled) (Research, Society and Development, 2023)
Introduction: Since antiquity, several treatments have been used to manage wounds. Currently, wound dressings with bacterial nanocellulose (BNC) have been used as treatment for tissue injuries, due to its biocompatibility, ability to maintain wound moisture, greater stimulation of keratinocytes, fibroblastos and lower infection rates. Objective: To analyze macroscopically and microscopically the healing process of wound induced in Wistar rats using a dressing composed of BNC membrane. Methods: Twenty Wistar rats were submitted to two incisions on the back, corresponding to Test Wounds (TW), treated with a dressing composed of BNC membrane, and Control Wounds (CW), treated with gauze and saline solution. The rats were randomly and equally divided into four groups of five rats, so that G1 corresponded to the group biopsied at 3 days postoperatively, G2 at 7 days, G3 at 14 days, G4 at 21 days. The material collected was used to make histological slides stained with Hematoxylin/Eosin and Masson’s Trichrome. Results: There was no purulent exudate, hemorrhage or abscess formation in either group. The contraction of the TW borders was statistically significant (p<0,05) compared to the CW. The TW showed a lower inflammatory response and an earlier rate of reepithelialization than CW, and exhibited an earlier reduction in theamount of fibroblastos, as well as an earlier formation and organization of collagen fibers. Conclusion: The use of BNC dressing promoted early contraction of the wound edge, lower inflammatory response, greater attraction of fibroblastos, collagen formation, and organization of collagen fibers, resulting in faster healing.